(untitled) (Laisvalaikio tyrimai, 2013)
The purpose of this research article is pursued by analysing and systematising the results of the recent research, drawing the vectors of organizational environment, the change in direction which would influence the phenomenon preventively. In this article the causes of mobbing are analysed in two ways: in individual and organizational aspects, in order to answer the question of how to reduce the risk of mobbing by managerial actions, taking into account these criteria. The role of organizational system is highlighted as a factor, determining the emergence of bullying in the work environment. The analysis of individual causes of mobbing reveals that the attacks related to bullying are more likely to occur on personalities with exceptional features. The dynamics of organizational and individual factors, which affects bullying in organization and escalation of mobbing, was determined. The systematised findings of the most recent and earlier research suggest the topics for new studies of mobbing in relations within work organizations. Keywords: mobbing, bullying, organizational system, individual, prevention.